A Modified Eigenstructure Assignment Technique for Finite Element Model Updating - S. Ziaei-Rad; M. Imregun (Shock and Vibration)
This article deals with an extended application of the constrained eigenstructure assignment method (CEAM) to finite element model updating. The existing formulation is modified to accommodate larger systems by developing a quadratic linear optimization procedure that is unconditionally stable. Further refinements include the updating of the mass matrix, a hysteretic damping model, and the introduction of elemental correction factors. Six numerical test cases, dealing with effects of damping and measurement noise, mode shape incompleteness, and discretization differences, were conducted in the case of a 3-D frame model with 114 coordinates. The performance of the CEAM was evaluated systematically for both the purpose of error location and the global correction of the initial model. The same cases were also studied using another model updating approach, namely the response function method (RFM). It was found that the CEAM had a number of distinct advantages, such as yielding a noniterative direct solution, requiring much less computing power, and providing acceptable results for cases, that could not he handled using the RFM.